"Trapped": Gender, Identities and PE - METCALFE, SARAH,NICOLA (2018)
Physical Education (PE) is one of the most gendered school subjects, and is historically based on a binary which normalises a difference between young men and young women. As young people develop through adolescence, their social lives are characterised by interconnected social fields, including schooling, sport and media. This study sought to explore how young people negotiate their gendered identities within, and across, these interconnected fields using a Bourdieusian analysis. I used a mixed-methods approach of collective case studies to answer three research questions: 1. What role does sport play in the ways young people negotiate their gendered identity? 2. What role do schooling and media messages play in reproducing gender norms for young people? 3. How does social class influence how young people understand sport and their gendered identity? My methods combined a content and narrative analysis of media messages produced by four online sports media outlets during Rio 2016 Olympic Games with case studies in three demographically different schools in North East England. In each school, Year 11 students completed a questionnaire about their participation in sport and physical activity, coupled with their views of masculinity and femininity. Following this, interviews with 70 young people (33 males, 37 females) were conducted which focused on how young people negotiate their gendered identities within different social fields. Using Bourdieusian concepts of habitus, field and capital, this study has shown that these young people are strongly influenced by rigid and stereotypical representations of masculinity and femininity which are often conflated with binary notions of biological sex. The internalisation of these norms within one’s gendered habitus has meant that many young people expressed a sense of being “trapped” by these rigid notions of “acceptable” gendered behaviours, and consequently reproduce an ideology of difference between masculinity and femininity. Sport is internalised as “natural” within young men’s habitus, where participation and excellence in the “right” sport can lead to the accrual of social status and popularity. In contrast, the “sporty” female is othered, and little capital can be accrued for female participation in sport. Instead, young women are pressured to presenting an image of a “healthy” female appearance (one which is often unattainable as both skinny and curvy) through a symbolic attention to the body. Many young women go to the gym, but do not engage in vigorous exercise when they are there. Within this thesis, I refer to young people playing the game of gender, whereby there are “rules”, tactics, referees and winners/losers. The expectations of the game differ depending on whether the individual is male or female, and also on one’s classed position. This metaphor demonstrates an awareness that young people can be simultaneously affected by both structure and agency. By using tactics and strategy to manipulate one’s own gendered identity, young people can show agency. However, the rewarding of stereotypical and binary representations of masculinity and femininity through capital often means that many young people feel pressure to reproduce normative behaviours which do not challenge the status quo of the doxa. This PhD paints a negative image of how schooling and PE reinforce gender norms which prevent many young people experimenting and exploring their own gendered identities. However, through challenging young people’s reflexivity during the interview process, I found that many young people can reflect on their behaviours, bringing the often-non-conscious habitus into consciousness. This suggests that to challenge taken-for-granted norms of the habitus, pedagogy and research must encourage this reflexivity and force young people to think about gender in ways they have not done before